2012
DOI: 10.1111/j.1442-2042.2012.03222.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of RENAL nephrometry score with outcomes of minimally invasive partial nephrectomy

Abstract: Abbreviations & AcronymsObjective: To evaluate the predictive value of the Radius, Exophytic, Nearness, Anterior, Location nephrometry scoring system and to investigate the influence of its individual components on perioperative outcomes of minimally invasive partial nephrectomy. Methods: Consecutive laparoscopic partial nephrectomy (n = 189) and robotic partial nephrectomy (n = 109) cases from 2007 through 2011 were retrospectively reviewed from our prospectively maintained database. Urological surgeons assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…Some studies have found an association of RNS with complications, 10,13 while other studies did not find a significant association. 14,26 Similarly, the association of the CCI with RAPN complications and hospital readmission rates is still debated.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some studies have found an association of RNS with complications, 10,13 while other studies did not find a significant association. 14,26 Similarly, the association of the CCI with RAPN complications and hospital readmission rates is still debated.…”
Section: Discussionmentioning
confidence: 94%
“…RNS has been associated with perioperative outcomes and complications in previous studies of small renal tumors and PN. [8][9][10] Despite the objectivity of RNS, this measure alone does not incorporate other patient-specific characteristics and comorbidities that may significantly complicate PN and surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A high R.E.N.A.L. nephrometry score was found to increase the risk of major complications following PN [14]. However, there have been no correlation studies of the development of RAP/RAVF after PN and the R.E.N.A.L.…”
Section: Discussionmentioning
confidence: 98%
“…recently, Kutikov et al [18] insisted that r.e.n.a.l nephrometry score could be used not only to assess the complexity of renal tumor but also to predict malignant and high-grade pathology before the operation. Many studies also have demonstrated that the r.e.n.a.l nephrometry score correlates with surgical outcomes such as WIt [19,20]. However, there is a report concluded that r.e.n.a.l nephrometry score does not accurately reflect eBl in laparoscopic and robotic partial nephrectomy [21].…”
Section: Discussionmentioning
confidence: 99%
“…and DaP nephrometry itself has no information about the anatomic location of tumor, while r.e.n.a.l nephrometry can include detail anatomic characteristics of tumor (i.e., anterior/posterior, nearness to the collecting system or touching the main vessels). especially in minimally invasive surgeries, anatomic location of tumor (e.g., anterior/posterior) could affect perioperative outcomes [20,25]. It might be a limitation of DaP nephrometry.…”
Section: Discussionmentioning
confidence: 99%